(untitled) (Bangladesh Journal of Medical Science, 2021)
Aim: This study was aimed to evaluate the association between serumD-dimer, serum Ferritin with disease severity in patents havingCOVID-19. Methods:Total 80 confirmed COVID-19 patients were enrolled in this cross sectional study. Samples were assessed by positive SARSCoV- 2 by RT-PCR testing and were collected from two tertiary Hospitals(IbnSina Medical College Hospital and Ibrahim Cardiac Hospital and Research Institute).We also performed CT findings of COVID patients with or without pulmonary involvement. COVIDpositive patients were divided into two groups (Group 1 and Group2) according to lungs involvement confirmed by CT-scan. In this analysis, several variables such as gender, age, D-dimer and serum ferritin were taken. Results: The Mean of D-dimer in Group-1 subjects was 4.26±3.60mg/L and in Group-2, this was 0.59±1.08mg/L. So D-dimer level was significantly raised in COVIDpneumonic patient (P value = <0.001). The mean of ferritin(554.65±515.841)ng/ml for pneumonic patient was also highly significant than the mean(133.70±109.22)ng/ml of COVID without pneumonia. Conclusion:D-dimer and S. ferritin were elevated in patients with COVID-19. These two reliable biomarkers are correlate with the disease severity and useful for better management of COVIDpositive patients. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.166-170